2022
DOI: 10.1016/j.jaim.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Panchgavya: A precious gift to humankind

Abstract: Panchgavya represents milk, urine, dung, ghee, and curd, derived from cow and serves irreplaceable medicinal importance in Ayurveda and traditional Indian clinical practices. In Ayurveda , Panchgavya treatment is termed as ‘Cowpathy’ . In India, the cow is worshipped as a god called ‘Gaumata,’ indicating its nourishing nature like a mother. Ayurveda recommends Panchagavya to treat diseases of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…It has been observed that the dung excreted from Indian cow possesses excellent antimicrobial activity as compared to that of Jersey, Holstein or buffalo against K. pneumonia and E. coli (Rajeshwari et al 2016). Cow dung and cow urine have been found to possess antifungal activity against Rhizopus stolonifera, Sclerotium rolfsii and Fusarium oxysporum (Jandaik et al 2015;Bajaj et al 2022). The indigenous Himachali Pahari cow has not been explored earlier for its nutrient enriched properties of cow dung and bene cial microbes present in it.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the dung excreted from Indian cow possesses excellent antimicrobial activity as compared to that of Jersey, Holstein or buffalo against K. pneumonia and E. coli (Rajeshwari et al 2016). Cow dung and cow urine have been found to possess antifungal activity against Rhizopus stolonifera, Sclerotium rolfsii and Fusarium oxysporum (Jandaik et al 2015;Bajaj et al 2022). The indigenous Himachali Pahari cow has not been explored earlier for its nutrient enriched properties of cow dung and bene cial microbes present in it.…”
Section: Introductionmentioning
confidence: 99%
“…The application of these liquid formulations in the farming sectors have been proven as an eco-friendly, eco-accommodating and contamination-free method that aids in providing essential macro and micronutrients to plants for their proper growth and development (Sakthivel et al 2022). Therefore, the use of panchgavya and jeevamruth as manure could enhance crop yields without harming the soil biodiversity, as well as pretence a great opportunity to substitute the use of inorganic fertilizers and agrochemicals in the agricultural sectors (Bajaj et al 2022). The aim of the project is to analyse the effectiveness of the liquid manures panchgavya (P) and jeevamruth (J) and their combination panchgavya + jeevamruth (P + J) given in different formats in the plants that were grown in eld and pots.…”
Section: )mentioning
confidence: 99%
“…138 A mixture of cow dung, urine, milk, ghee, and curd, called panchgavya or cowpathy, is a valuable medicine in Ayurvedic practices. Bajaj et al 139 declared that panchgavya has medicinal effects of antifungal, antibacterial, immunomodulation, skin tonic, and many others. This medicinal knowledge is exclusively claimed by Ayurvedic medicine.…”
Section: Animal Productsmentioning
confidence: 99%